ANALISIS POTENSI DAN KONTRIBUSI PAJAK SARANG BURUNG WALET TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN KUBU RAYA - Agustini, Yetty; Friani, Desi (Jurnal Ekonomi STIEP ( JES ), 2021)
The studies to be achieved in this research are: (1) To determine the potential of Swallo’s Nest Tax in Kubu Raya Regency. (2) This is to determine the contribution of Swallow’s Nest Tax to Regional Original Revenue in Kubu Raya Regency. The method used in this research is descriptive method. Based on the results of data analysis, several things can be concluded as follows:(1) The potential for Swallow’s Nest Tax in Kubu Raya Regency in 2019 is RP.1,366,120,000.00. When compared with the revenue target set by the Regional Government of Kubu Raya Regency with the potential for Swallow’s Nest Tax revenue in 2019 as a result of the author’s calculations, there is a very large difference of Rp.1,279,120,00.00. (2) The contribution of Swallow’s Nest Tax to Regional Original Revenue in Kubu Raya Regency from 2017 to 2019 is considered very poor.